Kształtowanie udziału ludności w dochodzie narodowym - Gomułowicz, Andrzej (Wydział Prawa i Administracji UAM, 1989)
Not before the majority of the society understands the sense of past, present and future social changes, will it be possible to talk about the sense of co-creating the future. The problems of tomorrow shoul be known to the whole society and not only to its intellectual elite, for everybody must participate in introducing changes which are to prevent the catastrophe. It is just in creating such unity that the sense of co-creating the future lies. The future of the mankind is not given „a priori"; instead, it is created in objectively favourable conditions. The future evokes both fear and hope. The fulfilment of hopes depends on the competent use of opportunities. It is only knowledge and the will of action that can prevent from wasting those opportunities. The future of the mankind consists not only in multiplying technical and technological devices, but in the first place requires that people be aware of aims and be willing to attain them. At our stage of development of the mankind, a main aim remains to be the change of social relations in the direction of a further harmonization of an individual development with collective forms of co-existence. Such is our nearest aim. The aims of future generations can by no means be foreseen at the moment. Fighting contradictions existing in both capitalist and socialist worlds is a complex process. Inherent features of capitalism, i.e. making people strive for profit and adopt a consumption-style way of living, do not promise long life to capitalist forms of coexistence. On the other hand, accumulated difficulties which the socialist countries have to cope with do not go along quick accomplishment of harmonizing a human personality with collective forms of existence. In such a case, co-creating the future, creating a new socio-economic formation on a global scale is a long-run and even distressing process. It seams that the present battle for peace is an important step in the process of changing human mentality for proper utilization of new productive forces in co-creating the future.
Shaping the participation of the population in national income